2018
DOI: 10.1007/s10096-018-3260-4
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem-vaborbactam: a carbapenem and beta-lactamase inhibitor with activity against carbapenem-resistant Enterobacteriaceae

Abstract: Meropenem-vaborbactam is a carbapenem and β-lactamase inhibitor combination that is newly indicated for the treatment of complicated urinary tract infections (cUTI), including adult pyelonephritis. Vaborbactam was developed due to emergence of carbapenem-resistant strains of Enterobacteriaceae. In a phase I trial, patients that received meropenem-vaborbactam 2-2 g intravenously over 3 h every 8 h, C was 58.2 ± 10.8 μg/mL for meropenem and 59.0 ± 8.4 μg/mL for vaborbactam. AUC was 186 ± 33.6 μg • h/mL for merop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…4) is the first FDA-approved β-lactamase inhibitor containing a cyclic boronate pharmacophore. [18][19][20][21] The design of vaborbactam is the result of medicinal chemistry efforts to develop a cyclic boronate analog with selectivity towards bacterial β-lactamases over mammalian serine hydrolases. X-ray crystallography studies confirmed that vaborbactam forms a covalent adduct with the catalytic serine residue of CTX-M-15 and AmpC.…”
Section: Vabomere® (Meropenem + Vaborbactam)mentioning
confidence: 99%
“…4) is the first FDA-approved β-lactamase inhibitor containing a cyclic boronate pharmacophore. [18][19][20][21] The design of vaborbactam is the result of medicinal chemistry efforts to develop a cyclic boronate analog with selectivity towards bacterial β-lactamases over mammalian serine hydrolases. X-ray crystallography studies confirmed that vaborbactam forms a covalent adduct with the catalytic serine residue of CTX-M-15 and AmpC.…”
Section: Vabomere® (Meropenem + Vaborbactam)mentioning
confidence: 99%
“…Carbapenems are considered to be reliable and effective antibiotic agents against most pathogenic bacteria because of their broad antibacterial spectrum [ 1 ] and are used in the treatment of serious nosocomial infections caused by cephalosporin-resistant bacteria [ 1 ]. Species of the Acinetobacter genus are extremely well adapted to the hospital environment and can easily become resistant to available antimicrobial agents; therefore, the isolation of carbapenem-resistant Acinetobacter species has raised increasing concerns [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenems are considered to be reliable and effective antibiotic agents against most pathogenic bacteria because of their broad antibacterial spectrum [1] and are used in the treatment of serious nosocomial infections caused by cephalosporin-resistant bacteria [1]. Species of the Acinetobacter genus are extremely well adapted to the hospital environment and can easily become resistant to available antimicrobial agents; therefore, the isolation of carbapenem-resistant Acinetobacter species has raised increasing concerns [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%